Hashimoto’s Encephalopathy Presenting with Unusual Behavioural Disturbances in an Adolescent Girl - Murugan Selvaraj Karthik; Kulothungan Nandhini; Viswanath Subashini; Ramasamy Balakrishnan (Case Reports in Medicine)
Hashimoto’s encephalopathy (HE) is a rare autoimmune disorder with neurological and neuropsychiatric manifestations and elevated titres of anti-thyroid antibodies. Here we are reporting a case of HE in a 19-year-old girl who presented with seizure-like episodes, confusion, and behavioural disturbances with catatonic symptoms such as posturing, echopraxia, echolalia, and ambivalence. Patient did not respond to antipsychotics and anticonvulsants. On further investigation, patient was found to have high serum anti-TPO antibodies of about 1261 U/mL with euthyroid status, which supported a suspicion of HE. Our consultant neurologist confirmed the diagnosis and she was started on injection of methylprednisolone 750 mg OD. Since patient started showing clinical improvement, her antipsychotic medications were tapered off. On follow-up, patient has recovered and is functioning well. Since HE is a diagnosis of exclusion, very high anti-TPO antibodies and good response to steroids supported the diagnosis of HE in this patient after excluding other etiological possibilities. This case has been reported because the clinical presentation was predominantly neurobehavioural manifestations which is uncommon with HE.